Alummouth Wash as an Adjunctive Treatment in Chronic Periodontits (Mustansiria Dental Journal, 2018)
The term of (Alum) refers to various isomorphous double sulfates composed oftrivalent and univalent metals, especially aluminum potassium sulfate, KAl(SO4)2·12H2O, Alum as a compound has been used in past to treat different oral andmedical conditions. Using of alum as a mouth wash in periodontology was notcompletely explored and only a few studies were carried out regarding this subject.This study was carried out to observe the effect of alum as an adjunctive therapy inperiodontitis.One hundred twenty patients with chronic periodontitis were randomly allocatedinto four groups. The first group treated with conventional root planing procedureusing periodontal curette. The other three groups were treated with the sameconventional procedure followed by twice a day mouth rinse with differentconcentrations of Alum solutions for three weeks after root planing. Means of PLI, GI& PD were calculated for the participants before treatment and three weeks after.Results of this research showed a significant decrease in all study parameters in allgroups with significant differences between the two different modalities of treatment.Alum solution can be a good adjunctive treatment for chronic periodontitis, butmore studies are needed on both short and long terms.